Writing good abstracts - Alexandrov, Andrei V.; Hennerici, Michael G. (Cerebrovascular diseases, 2007)
INTRODUCTION: Writing an abstract means to extract and summarize (AB - absolutely, STR - straightforward, ACT - actual data presentation and interpretation). Thousands of abstracts are submitted to stroke conferences each year. The following suggestions may improve the chances of your work being selected for presentation, and to communicate results in the most efficient and unambiguous way. TITLE AND STRUCTURE: Make the title dynamic and informative, rather than descriptive. Structure the abstract following the IMRaD (Introduction, Methods, Results and Discussion) principle for your future original paper where background would become Introduction and conclusions would enter Discussion. Select the appropriate category for submission carefully. This determines which experts grade the abstract and the session where your competitors represent their work. If selected appropriately, your abstract is more likely to be graded by peers with similar interests and familiarity with your work or field. Methods should describe the study design and tools of data acquisition shortly, not data. - RESULTS: Provide data that answer the research question. Describe most important data with numbers and statistics. Make your point with data, not speculations and opinions. Abbreviations should be avoided and only be used after they have been spelled out or defined. Common mistakes include failure to state the hypothesis, rationale for the study, sample size and conclusions. Highlight the novelty of your work by carefully chosen straightforward wording. - CONCLUSIONS: Conclusions have to be based on the present study findings. Make sure your abstract is clear, concise and follows all rules. Show your draft to colleagues for critique, and if you are not a native English speaker show it to a person who can improve/correct your text. Remember that accepted abstracts of completed original research should be followed by published original papers - if this is not intended or fails, it may indicate an impaired ability to succeed in scientific writing and an academic career.